A Tactical Periodization Approach for Rugby Union. Issue 5 (October 2018) - Tee, Jason C.; Ashford, Michael; Piggott, David
Abstract : ABSTRACT: THE CONCEPT OF TACTICAL PERIODIZATION HAS BEEN POPULARIZED BY A NUMBER OF SUCCESSFUL, HIGH-PROFILE SOCCER COACHES. MORE RECENTLY, REPORTS HAVE INDICATED THAT TACTICAL PERIODIZATION APPROACHES ARE BEING USED WITHIN ELITE RUGBY UNION. HOWEVER, FEW REPORTS CURRENTLY EXIST, AND RESOURCES FOR COACHES INTERESTED IN USING A TACTICAL PERIODIZATION APPROACH ARE LIMITED. THIS ARTICLE AIMS TO DEMONSTRATE HOW TACTICAL PERIODIZATION CAN BE APPLIED IN RUGBY UNION TO HELP COORDINATE LONG-TERM PLANNING, IMPROVE THE SPECIFICITY OF TRAINING, AND PREPARE PLAYERS MORE EFFECTIVELY FOR COMPETITION.